Inter-industry trade and business cycle dynamics - Wolfgang Lechthaler; Mariya Mileva (Kiel Institute for the World Economy (IfW), 2016)
Motivated by the increased importance of trade between industrialized and less-developed countries, we build a DSGE model featuring comparative advantage and inter-industry trade to analyze business cycle dynamics of industrialized countries. We show that productivity shocks lead to shifts in the relative demand of exporting and import-competing sectors, implying an important role for the mobility of workers across sectors. If workers are very mobile, then the aggregate implications of the two-sector model are similar to a one-sector model. If workers are very immobile, then the two-sector model features smaller responses in GDP to domestic shocks but larger responses to foreign shocks, implying larger comovement of GDP across countries.
Keywords: E20; E25; F41; F44; F62; 330; international business cycles; inter-industry trade; comparative advantage; wage inequality